La descripción en el relato de viajes: los tópicos - Ortega Román, Juan José (Revista de Filología Románica, 2006)
Although there are several years between a lot of travel books, even if they are from different writers and different countries, we think that it’s possible to find some amazing coincidences in most of them. It’s common to see how descriptions about cities, countries, museums, libraries, traditions or schools, shows very often a curious coincidence and can be also transferred from one writer to another one. Can we research these productions looking for a same original text?